PHARMACOLOGICAL POTENTIAL OF BIOACTIVE COMPOUNDS FROM LACTIC ACID BACTERIA ISOLATED FROM FERMENTED FOOD WASTE AGAINST PSEUDOMONAS SPECIES - Mahalakshmi S; Devasena B; Swetha M; Rubala Nancy; Janaki M (The Bioscan, 2025)
Lactic Acid Bacteria producing bioactive compounds were isolated from semi rotten beans, idly flour and yoghurt. The isolated compound exhibited antibacterial activity against Pseudomonas species using agar spot test. The isolates that are obtained from the different sources grow in the medium nearly 6 to 7 pH, in which they produced bioactive compound extracellular at the highest level. The level of these compounds get increased in the medium with respect to the increase in bacterial growth. This study is to investigate the standardization of cultural conditions such as medium, pH and temperature that are needed for maximum antibacterial compound production and their stability against wide range of pH and temperature and also the evaluation of antibacterial compound activity